STRATEGI PERENCANAAN KARIR UNTUK MENINGKATKAN MANAJEMEN SUMBER DAYA MANUSIA BERKINERJA TINGGI MELALUI MANAJEMEN TALENTA SEBAGAI VARIABEL MEDIATOR - Rosita, Sry; Tialonawarmi, Feny (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
Strategies on career planning will create high-performance human resource management. The main objective of this research is to apply a strategy to career planning so as to improve high-performance human resource management through talent management.The research design uses survey research with 3 (three) purposes of description, explanation and exploration. The research target is BUMN employees totaling 267. Methods of data collection by providing a structured questionnaire aimed at the respondents. The analytical tool used in this study is Partial Least Square (PLS) and the software used is smart-PLS. The results of the study show that strategies in career planning can improve high-performance human resource management, followed by the role of strategies on career planning in improving talent management, and talent management in improving high-performing human resource management, but the role of talent management as a mediator variable is smaller if than not mediated.